THE USE OF REFERENCE THROUGH "ABOUTNESS" USING GREGORY CARLSON'S CONCEPT IN SONG LYRICS OF CELINE DION ALBUM: FALLING INTO YOU - Aprilia Anzani,; Charles David Marudut Silalahi,; Kezia Meily Nicharisa Sembiring, (Jurnal Cakrawala Ilmiah, 2025)
This study looks at how Gregory Carlson's concept of "aboutness" is used in the lyrics of Celine Dion's album Falling Into You. The study employs qualitative analysis to examine how linguistic tropes, such as demonstratives, metaphors, and symbolic imagery, convey themes of love, grief, and resiliency and arouse strong emotions. Aboutness enhances the album's thematic depth by tying abstract emotions to potent mental imagery, as demonstrated in songs like "It's All Coming Back to Me Now" and "Because You Loved Me." The significance of language systems for improving musical narrative and emotional expression is shown by this study.